Integrasi Islam dan Budaya Arab di Indonesia - Trei Ilham Supawi; Badrun Badrun (Medan Resource Center, 2022)
Arab culture is still disputed and debated until now, because it is not the original innate religion of Islam in Arabia but pre-Islamic Arab culture. Various cultures enter Indonesia, and some of them state and admit that culture is a characteristic or identity of Islam. This study will explain about the study of the integration of Islam with the Arabic culture that developed in Indonesia, such as the culture of the veil or turban and the gambus music. The methods used in this study are qualitative library research and historical methods, which the researchers will conduct a study into various kinds of literature related to Islam and Arabic culture in Indonesia by trying to see the past based on the data obtained. The results found that there are some Muslims that still maintain a culture of veils for women and turbans for men in Indonesia, which at first became a culture of Arab society turned into a trend or style, and Gambus music attached to the events with Islamic nuances also contributed to this integration. Through this research, it will find in theoretically about the integration of Islam and Arab culture in Indonesia as well as the practices that occur.